Modulation of aberrant crypt foci and apoptosis by dietary herbal supplements (quercetin, curcumin, silymarin, ginseng and rutin) - Suresh R. Volate; Destiny M. Davenport; Stephanie J. Muga; Michael J. Wargovich (2005)
It is estimated that one-third of Americans use dietary herbal supplements on a regular basis. Diets rich in bioactive phytochemicals are associated with reduced risk of certain cancers, notably, colon cancer. Herbal supplements have not been directly tested as sources of bioactive cancer preventives. Hence, this study compares the ability of four herbal flavonoids (quercetin, curcumin, rutin and silymarin) and one whole herb mixture (ginseng powder) to suppress aberrant crypt foci (ACF) in an azoxymethane (AOM)-induced rat colon cancer model. Second, this study examines the effect of these herbal compounds on apoptosis and the mechanisms by which these compounds evoke apoptosis. The results of this study show that diets containing quercetin, curcumin, silymarin, ginseng and rutin decreased the number of ACFs by 4-, 2-, 1.8-, 1.5- and 1.2-fold, respectively compared with control. Histological analysis of the colon mucosa revealed that all the herbal supplements, except silymarin, induced apoptosis, with quercetin being the most potent (3× increase compared with control). Furthermore, ginseng and curcumin were region-specific in inducing apoptosis. The ability of quercetin and curcumin to modulate ACFs correlates well with their ability to induce apoptosis. Western blot analysis of caspase 9, Bax (proapoptotic) and Bcl-2 (antiapoptotic) proteins from the colon scraping suggests that quercetin and curcumin induce apoptosis via the mitochondrial pathway. Taken together, the results of this study suggest that these herbal supplements may exert significant and potentially beneficial effects on decreasing the amount of precancerous lesions and inducing apoptosis in the large intestine.